Effects of Dietary Tuber Ethanolic Extract of Nut Grass (Cyperus rotundus Linn.) on Growth, Immune Response, and Disease Resistance in Nile Tilapia (Oreochromis niloticus) - Supranee Wigraiboon; Ruamruedee Panchan; Vijitra Luang-In; Wilailak Ounjit; Paiboon Panase; Sontaya Sookying; Nantaporn Sutthi (Animals, 2024)
Nut grass (Cyperus rotundus Linn.) is a weed that grows in all tropical, subtropical and temperate regions of the world, including areas where it grows on saline soil. This research was conducted to evaluate the effect of C. rotundus tuber extract in the diet on the growth performance and disease resistance of Nile tilapia. Various components of phytochemical importance of nut grass, including sugars/carbohydrates, terpenoids, tannins, and flavonoids were found in C. rotundus. Tilapia (n = 25 fish/group in triplicate) were fed with different levels of nut grass extract including 0 (control; T1), 0.4 (T2), 0.8 (T3), and 1.6 (T4) g/kg for 60 days in a completely randomized design (CRD) experiment. After the feeding trial, the highest weight gain and average daily gain (ADG) were observed in the T4 group, but it was not significantly different from T3 (Nile tilapia fed with a 0.8 g/kg) (p > 0.05). The lowest feed conversion ratio (FCR) was observed in the T3 group. Moreover, the fillet, crud lipid content, and blood chemical profiles (aspartate aminotransferase (AST), cholesterol, and malondialdehyde (MDA)) in fish fed with 1.6 g/kg were highest when compared in all groups. In addition, the T3 group presented with the immune response parameter found in red blood cells (RBC), lysozyme activity, and antioxidant (superoxide dismutase activity (SOD)) being higher than those of the control group (p < 0.05). The highest survival (93.33%) was observed in fish fed with 0.8 g/kg (T3) after a 14 day challenge with Streptococcus agalactiae. Thus, it was concluded that nut grass extract at 0.8 g/kg can be used to improve the growth performance and the tendency for resistance to S. agalactiae in Nile tilapia.